(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
For historical reasons, teaching the German language in our country was widespread and had long-standing socio-cultural traditions. At present, the German language is increasingly being replaced by the English language. One of the main problems in teaching German was the lack of understanding of students in the need to learn German, the lack of motives among students when teaching German. Therefore, the question of how to motivate students in teaching German is one of the most urgent for me as a teacher. This article covers theoretical information on innovative methods of teaching German as well as motivating students to learn German.